PEMBERDAYAAN KOMUNITAS MELALUI PENANAMAN TOGA BERBASIS KESEHATAN DAN LINGKUNGAN - Husnirrahman J; Armiwaty Armiwaty; Raeny Tenriola Idrus (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2026)
This community engagement program was carried out at MTs Nurfadhilah, Somba Opu District, Gowa Regency, an educational environment with strong ecological potential yet underutilized for the development of Family Medicinal Plants (TOGA). The presence of unmanaged open spaces reflects limited greening initiatives and low levels of knowledge among students and the surrounding community regarding TOGA as a means of promoting self-care and natural health practices. The primary issues include insufficient education on medicinal plants, limited skills in basic cultivation and herbal processing, and low awareness of environmental stewardship. The program addressed these challenges through a series of activities: dissemination of information on the benefits of TOGA, training in sustainable and accessible cultivation techniques—such as vertical gardens and simple hydroponics—workshops on processing herbal products (tea, jamu, and simplicia), and continued mentoring for transforming school land into a functional TOGA garden. Simple technological applications, including QR codes on plants, were introduced to enhance digital herbal literacy. The implementation methods consisted of outreach, training, appropriate technology application, mentoring, and evaluation. The program is expected to improve participants’ knowledge and skills, optimize school spaces as productive green landscapes, and foster a culture of self-reliant health practices rooted in the use of herbal plants.